2006
DOI: 10.1177/147323000603400411
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Oxidants and Antioxidants in Acute Ischaemic Stroke

Abstract: Plasma levels of the oxidants xanthine oxidase, nitric oxide and malondialdehyde and the antioxidants superoxide dismutase, glutathione peroxidase and glutathione reductase, together with total superoxide scavenger activity and nonenzymatic superoxide scavenger activity, were determined in 19 patients with acute ischaemic stroke and 20 controls. Compared with controls, superoxide dismutase, total superoxide scavenger activity, glutathione peroxidase and glutathione reductase activities were significantly lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 24 publications
3
18
1
1
Order By: Relevance
“…The result is consistent with the previous report that plasma SOD and glutathione peroxidase activities were significantly decreased and malondialdehyde levels were significantly increased in patients with acute ischaemic stroke. The reduced SOD activity may be related to the exhaustion of this antioxidant by the challenge of free radical stress [20]. However, SOD activity was increased in a dose‐dependent way after the pre‐treatment of rats with protopine.…”
Section: Discussionmentioning
confidence: 99%
“…The result is consistent with the previous report that plasma SOD and glutathione peroxidase activities were significantly decreased and malondialdehyde levels were significantly increased in patients with acute ischaemic stroke. The reduced SOD activity may be related to the exhaustion of this antioxidant by the challenge of free radical stress [20]. However, SOD activity was increased in a dose‐dependent way after the pre‐treatment of rats with protopine.…”
Section: Discussionmentioning
confidence: 99%
“…Demirkaya et al (2001) found that red blood cell GPx activity decreased in the first 24 hours after the onset of stroke symptoms as compared with the control group. Aygul et al (33) also observed that GPx activity in plasma and red blood cells decreased in IS patients.…”
Section: Discussionmentioning
confidence: 91%
“…m 12, 66) m 10,18,38,49,61,168,180,195,220,277) À TBARS m 79,191,214) m 214,273) m 25,79) m 3, 45,81,77,213) …”
Section: Parkinson's Diseaseunclassified